Effects of Dietary Carbohydrate to Lipid Ratios on Growth Performance, Muscle Fatty Acid Composition, and Intermediary Metabolism in Juvenile Black Seabream (Acanthopagrus schlegelii) - Taj, Sehrish; Irm, Misbah; Jin, Min; Yuan, Ye; Andriamialinirina, Hardy Joël Timothée; Zhou, Qicun (Frontiers in Physiology, 2020)
In the past few years, many aspects of juvenile black sea bream (Acanthopagrus schlegelii) culture have been highly developed and optimized but the dietary carbohydrate and lipid (CHO: L) ratios for optimal growth has never been evaluated. Hence, to study the effect of dietary CHO: L ratios on growth and intermediary metabolism in black sea bream, five experimental diets with different dietary CHO: L ratios ranged from 0.33 to 3.75 were fed to apparent visual satiety to triplicate groups of twenty fish (initial weight 0.51±0.02g). Fifteen tanks were randomly assigned one of the five diets. After 8 week feeding trial, the high specific growth rate (SGR) was observed in fish fed on diets containing the CHO: L ratios of 1.36. The low levels of serum triglyceride and cholesterol were observed in the group fed with the CHO: L ratios of 2.26 and 3.75. Hepatic gene expression data for glucose metabolism indicated that glucose transport (glut2) and glycolysis (gk), induced in liver by the high carbohydrate diet. While the higher mRNA expression level of lipogenic genes (fas and accα) and lower mRNA expression of FA β-oxidation genes (cpt1 and acox1) were observed in the high CHO: L ratios diets. Despite the minor change in n-3 PUFA muscle content in the fish fed high CHO: L ratios diets, this fish still remains a rich in n-3 PUFA product and typically maintained its nutritional value. Finally, our research indicated that dietary carbohydrates have a stronger impact on hepatic lipid accumulation than dietary lipids. High dietary CHO: L ratios (> 1.36) enhanced the hepatic lipid deposition by increasing de novo lipogenesis and decreasing FA β-oxidation and suggest a maximal dietary CHO: L ratios of 1.36 for both optimal growth and feed utilization without compromising flesh quality. Further these findings could confer to broaden the understanding of the physiological metabolism of dietary CHO: L ratios for black sea bream